Immunosuppressive drugs impairs antibody response of the polysaccharide and conjugated pneumococcal vaccines in patients with Crohn's disease. Issue 41 (5th October 2015) - Kantsø, Bjørn; Halkjær, Sofie Ingdam; Thomsen, Ole Østergaard; Belard, Erika; Gottschalck, Ida Benedikte; Jørgensen, Charlotte Sværke; Krogfelt, Karen A.; Slotved, Hans-Christian; Ingels, Helene; Petersen, Andreas Munk
Highlights PCV13 and PPV23 were studied in Crohn's disease patients. PCV13 induces higher serotype specific antibody response in Crohn's disease patients than PPV23. Immunosuppressive drugs impaired the antibody response to PCV13 and PPV23. TNF-α antagonist further impaired the response to PCV13 and PPV23.